Case Study of Teaching Meta Communicative Competence Issues in Learners with ID - Sholpan, Saimkulova; Assel, Chaklikova; Odanova, S.A.; Rakhmatova, R.; Taniya, Kapessova (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Nowadays, the fact of lack of knowledge of bilingualism due to the changed volume ratio in the teaching of writing is becoming more and more apparent, especially to learners with intellectual disabilities. The emergence of complex processes marks this fact is interference and convergence of speech, which are sources of better speaking and writing in bilingualism. The purpose of the study is to identify the specific difficulties of teaching writing to younger bilingual schoolchildren with ID and to develop a productive speech therapy system for the prevention and correction of violations of higher mental functions that they have. The object of research is the features of teaching children with speech deficiency and with ID to writing in bilingual conditions. The subject of the research is the process of preventing and overcoming problems in the bilingual conditions of teaching children with speech and ID functions deficiency.